The Influence of the Jigsaw Cooperative Learning Model and Learning Motivation on Student Science Learning Outcomes - Nadrah Nadrah (CV. AFDIFAL MAJU BERKAH, 2023)
This study aims to determine the effect of the model jigsaw cooperative learning and learning motivation on student learning outcomes class VI science subject at SD Inpres 2 Tidung. Researchers use the approach post test only control group design, which was carried out on 40 class VI students as a sample (object) of the researcher, consisting of 20 people as the experimental group and 20 people as the control group. For obtain data about learning outcomes using learning outcomes tests, while data about learning motivation using a learning motivation questionnaire. Data analysis using two-way analysis of variance and tukey (Q) test . The results of the study showed that (1) the students' learning outcomes in science were following the jigsaw cooperative learning model is higher than students who follow the conventional learning model, (2) students who have high learning motivation there is a difference in science learning outcomes between students who follow the jigsaw cooperative learning model with students who follow conventional learning models. (3) students who have learning motivation low there is a difference in science learning outcomes between students who follow the model jigsaw cooperative learning with students following the model conventional learning, and (4) there is an interaction effect between models learning by having learning motivation towards science learning outcomes.